Students Emotional Intelligence as Catalisator for Academic Achievement - Muhammad Refki Novesar (Department of Management - Institut Shanti Bhuana, 2020)
Education is very important, in measuring signings one's activity in the world of education that can be seen from the academic achievement, in shaping the students ' academic achievements influenced by many things one of them is intellectual intelligence, which only affects 20% of his own accomplishments influenced by other factors, one of which is emotional intelligence, as emotional intelligence will help every learner in their learning and know their ideals and the steps they have traveled. This study saw how the relationship between emotional intelligence to the academic oprestation owned by a student, using a regression test in 105 student samples, selected by purposive sampling, i.e. active students, obtained overall results of emotional intelligence giving a significant and positive influence towards student academic achievement, for which students can improve the ability of emotional intelligence to be able to provide better academic achievement. of the results , to see what dimensions provide a positive and significant relationship to be researched in the form of a dimension possessed by emotional intelligence, whereby each dimension delivers a significant and posotive outcome, which gives meaning, every student should raise all of the emotional intelligence to be able to improve performance.